2006
DOI: 10.1073/pnas.0607443103
|View full text |Cite
|
Sign up to set email alerts
|

A beta2-frequency (20–30 Hz) oscillation in nonsynaptic networks of somatosensory cortex

Abstract: Beta2 frequency (20 -30 Hz) oscillations appear over somatosensory and motor cortices in vivo during motor preparation and can be coherent with muscle electrical activity. We describe a beta2 frequency oscillation occurring in vitro in networks of layer V pyramidal cells, the cells of origin of the corticospinal tract. This beta2 oscillation depends on gap junctional coupling, but it survives a cut through layer 4 and, hence, does not depend on apical dendritic electrogenesis. It also survives a blockade of ␣-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
276
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(310 citation statements)
references
References 28 publications
(45 reference statements)
28
276
3
Order By: Relevance
“…Correspondingly, the fast time course of the nested -and ␤/␥-oscillations requires a mature GABAergic system (33) that develops between P10 and P15 in rat cortex (34). The differential effect of GABA A blockade on ␥-and ␤-oscillations in the current study has also been found for kainate-induced cortical ␤/␥-activity in vitro for later developmental stages (35). The reduction in ␥-oscillations is in line with an inhibitory interneuron microcircuit in layer 2/3 that is responsible for ␥-activity (32).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Correspondingly, the fast time course of the nested -and ␤/␥-oscillations requires a mature GABAergic system (33) that develops between P10 and P15 in rat cortex (34). The differential effect of GABA A blockade on ␥-and ␤-oscillations in the current study has also been found for kainate-induced cortical ␤/␥-activity in vitro for later developmental stages (35). The reduction in ␥-oscillations is in line with an inhibitory interneuron microcircuit in layer 2/3 that is responsible for ␥-activity (32).…”
Section: Discussionsupporting
confidence: 54%
“…The reduction in ␥-oscillations is in line with an inhibitory interneuron microcircuit in layer 2/3 that is responsible for ␥-activity (32). The enhancement of ␤-power could result from a change in local microcircuit dynamics (36), an ''uncovering'' of ␤-generation from deeper layers (35), or simply reflect a frequency component arising from the ictal spikes. The sensitivity of the dynamics to the NMDA and not the AMPA receptor antagonists early during development suggests an immature glutamatergic network (4), whose temporal dynamics is mainly determined by the fast inhibition.…”
Section: Discussionmentioning
confidence: 91%
“…The center frequency (f) for each low frequency rhythm was defined as the largest peak of the average Gaussians with a: 5 f 13 Hz, b1: 13 < f 24 Hz and b2: 24 < f < 30 Hz. Low frequency rhythms were detected in classic sensorimotor a and b1 bands (5 a 13 Hz, 13 < b1 24 Hz) and a b2 rhythm (24 < b2 < 30 Hz) was found in 7 out of 8 subjects (b2 rhythms have previously been shown in layer V of somatosensory cortex [Roopun et al, 2006]). …”
Section: Ecog Analysismentioning
confidence: 84%
“…The role of axonal gap junctions has been investigated in relation to physiological and possibly pathological alterations of electrical activities of the brain, including ␤2 oscillations (20-30 Hz), ␥ oscillations (30-70 Hz), and very fast oscillations (Ͼ100 Hz) (6)(7)(8)(9)(10)(11)35). Oscillations at 250-300 Hz have been recorded in sclerotic human hippocampus, surgically removed and studied in vitro (36).…”
Section: Discussionmentioning
confidence: 99%
“…Schmitz and colleagues (7) provided electrophysiological and dye coupling evidence for axoaxonic gap junctions in CA1 and CA3 pyramidal cells as well as in dentate granule cells. Subsequently, both modeling and in vitro experimental data suggested that axonal gap junctions could account for very fast oscillations (Ͼ70 Hz), including Ϸ200-Hz ripples (8,9) as well as play a critical role in the generation of persistent ␥ (30-70 Hz) (10) and neocortical ␤2 (20-30 Hz) oscillations (11). However, definitive ultrastructural evidence for gap junctions in cortical principal cells has been elusive.…”
mentioning
confidence: 99%